2021
DOI: 10.3390/s21072568
|View full text |Cite
|
Sign up to set email alerts
|

Common-Mode Voltage Reduction in Capacitive Sensing of Biosignal Using Capacitive Grounding and DRL Electrode

Abstract: A capacitive measurement of the biosignals is a very comfortable and unobtrusive way suitable for long-term and wearable monitoring of health conditions. This type of sensing is very susceptible to noise from the surroundings. One of the main noise sources is power-line noise, which acts as a common-mode voltage at the input terminals of the acquisition unit. The origin and methods of noise reduction are described on electric models. Two methods of noise removal are modeled and experimentally verified in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…However, this approach requires a larger circuit layout area, which is unsuitable for developing a small-volume open-loop fiber-optic gyroscope. It has been found that most noise results from the gyro’s electric source and ground wire [ 22 ], which is independent of the modulation polarity. According to Equation (12), because J 1 ( ϕ m ) is an odd function, the error can be easily eliminated by flipping the modulation polarity regularly and changing the output polarity simultaneously.…”
Section: Demodulation and Control Algorithmmentioning
confidence: 99%
“…However, this approach requires a larger circuit layout area, which is unsuitable for developing a small-volume open-loop fiber-optic gyroscope. It has been found that most noise results from the gyro’s electric source and ground wire [ 22 ], which is independent of the modulation polarity. According to Equation (12), because J 1 ( ϕ m ) is an odd function, the error can be easily eliminated by flipping the modulation polarity regularly and changing the output polarity simultaneously.…”
Section: Demodulation and Control Algorithmmentioning
confidence: 99%
“…A number of investigations are currently underway to overcome the issues associated with measuring signals from the human body and existing signal measurement methods. In this Special Issue, four articles focus on this issue [ 5 , 6 , 7 , 8 ]. Ben Atitallah B. et al present a systematic comparison of methods for bioimpedance spectroscopy (BIS) measurement, including the use of a gain phase detector (GPD), IQ demodulation, and fast Fourier transform (FFT), with a focus on magnitude and phase measurement accuracy, signal processing, hardware and software complexity, and power consumption [ 5 ].…”
mentioning
confidence: 99%
“…Bednar T. et al explored the use of capacitive bio-signal measurement for long-term and wearable monitoring but highlighted its susceptibility to environmental noise, particularly power-line noise. Their paper describes the origin of noise and proposes two electric models for its reduction: a passive capacitive grounding electrode and an active capacitive driven right leg (DRL) electrode [ 8 ].…”
mentioning
confidence: 99%